Use of public health service increased risk kidneys in pediatric renal transplant recipients. (4th July 2019) - Meyers, Melissa R.; Shults, Justine; Laskin, Benjamin; Porrett, Paige; Levine, Matthew; Abt, Peter; Amaral, Sandra; Goldberg, David S.
Abstract: With the opioid epidemic and expansion of "IR" classification, 25% of deceased donors are categorized PHS‐IR. Studies have assessed utilization of PHS‐IR organs among adults, but little is known about pediatric recipients. This retrospective cohort study from 2004‐2016 (IR period) aimed to: (a) assess IR kidney utilization patterns between adults and children; (b) identify recipient factors associated with transplant from IR donors among pediatric kidney recipients; and (c) determine geography's role in IR kidney utilization for children. The proportion of pediatric recipients receiving IR kidneys was significantly lower than adults ( P  < 0.001), even when stratified by donor mechanism of death (non‐overdose/overdose) and era. In mixed effects models accounting for clustering within centers and regions, older recipient age, later era (post‐PHS‐IR expansion), and blood type were associated with significantly higher odds of receiving an IR kidney (17 years era 5: OR 5.16 [CI 2.05‐13.1] P  < 0.001; 18‐21 years era 5: OR 2.72 [CI 1.05‐7.06] P  = 0.04; blood type O: OR 1.32 [CI 1.06‐1.64] P  = 0.013). The median odds ratio for center within region was 1.77 indicating that when comparing two patients in a region, the odds of receiving an IR kidney were 77% higher for a patient from a center with higher likelihood of receiving an IR kidney. Utilization of PHS‐IR kidneys is significantly lower among pediatric recipients versus adult counterparts. More work is needed to understand the reasons for these differences in children in order to continue their access to this life‐prolonging therapy.